β-frutofuranosidases em coleópteros: caracterização funcional e produção heteróloga de uma β-frutofuranosidase de Sphenophorus levis - Pedezzi, Rafael (2015)
The sugar cane represents one of the most Important agricultural segments in Brazil, which is the largest producer and exporter of sugar in the world as well the second largest ethanol producer. The Sphenophorus levis (Curculionidae) is an important sugarcane pest which lacks effective methods of control. The larvae of this insect feed the sugar cane plant decreasing productivity and causing the plant death. In view of identify the insect digestive arsenal enzymes, a transcriptome study was previously performed from S. levis larvae. Thereby, an invertase (P-fructofuranosidases class) coding sequence was identified and characterized. Considering the scarcity of functional studies on insect P-fructofuranosidases and their apparent non-occurrence among coleopterans, the aim of the present study was to investigate the occurrence and characterize the P-fructofuranosidase transcript identified. To validate that the P-fructofuranosidase sequence (herein denominated Sl-fi-fruct) is indeed encoded by the S. levis genome, PCRs were performed using genomic DNA extracted from the larval fat body as well as DNA from the midgut with microbial content. Amplification of Sl-fi-fruct gene using larval fat body DNA indicated its presence in the insect's genomic DNA. Quantitative PCR (qRT-PCR) analyses indicated that the production of mRNA only occurs in the midgut and reaches the greatest expression level in 30-day-old larvae, which is the expected pattern for digestive enzymes. Chromatography of glycosidases from S. levis midguts showed two enzymes acting as P-fructofuranosidase, indicating the presence of a Sl-fi-fruct isoform or a P-fructofuranosidase from insect intestinal microbiota. Moreover, it was found that a-glucosidases do not act on sucrose hydrolysis. Phylogenetic analyses indicated this enzyme to be similar to enzymes found in other coleopteran and lepidopteran P-fructofuranosidases, but also closely similar to bacterial enzymes, suggesting potential horizontal gene transfer. Despite this, the enzyme seems to be restricted to different groups of bacteria, which suggests distinct origin events. The Sl-fi-fruct gene was cloned in Pichia pastoris to produce the recombinant enzyme (rSl-P-fruct). Molecular weight of the recombinant protein was about 64 kDa, indicating possible glycosylation, since the theoretical weight was 54.8 kDa. The substrate specificity test revealed that rSl-P-fruct hydrolyzes sucrose and raffinose, but not melibiose or maltose, thereby confirming invertase activity. The pH curve revealed greatest activity at pH 5.0, demonstrating rSl-P-fruct to be an acidic P-fructofuranosidase. The enzymatic characterization was done and the optimum temperature was 50 °C, thermal resistance at 36 °C and pH maximum resistance at 6.0. The Michaelis-Menten curve showed Km=20.02 μM, Kcat=520.9 s-1 and Vmax=105.7 μM.s-1. 5 mM of SDS and MgCl2 cause inhibition of rSl-β-fruct activity. The present study expands the concept of the occurrence of P-fructofuranosidase in insects. Despite the few descriptions of this gene in the animal kingdom, it is possible to state that P-fructofuranosidase is crucial to the establishment of some insects throughout their evolutionary history, especially members of the Lepidoptera and Coleoptera clades. Considering the rSl-P-fruct potential to industrial application, they are promising if the thermal properties are improved.